Hydrogen Sulfide in the RVLM and PVN has No Effect on Cardiovascular Regulation - Streeter, Eloise; Al-Magableh, Mohammad; Hart, Joanne L.; Badoer, Emilio (Frontiers in Physiology, 2011)
Hydrogen Sulphide (H2S) is now recognised as an important signalling molecule and has been shown to have vasodilator and cardio-protectant effects. More recently it has been suggested that H2S may also act within the brain to reduce blood pressure. In the present study we have demonstrated the presence of the H2S producing enzyme, cystathionine  synthase (CBS) in the rostral ventrolateral medulla (RVLM) and the hypothalamic paraventricular nucleus (PVN), brain regions with key cardiovascular regulatory functions. The cardiovascular role of H2S was investigated by determining the blood pressure (BP), heart rate (HR) and lumbar sympathetic nerve activity (LSNA) responses elicited by a H2S donor (NaHS, sodium hydrogen sulphide) or inhibitors of CBS, microinjected into the RVLM and PVN. In anaesthetised WKY rats bilateral microinjections of NaHS (0.2 – 2000 pmol/side) into the RVLM did not significantly affect BP, HR or LSNA, compared to vehicle. Similarly, when the CBS inhibitors, amino-oxyacetate (AOA) (0.1 – 1.0 nmol/side) or hydroxylamine (HA) (0.2 – 2.0 nmol/side), were administered into the RVLM, there were no significant effects on the cardiovascular variables compared to vehicle. Microinjections into the PVN of NaHS, HA and AOA had no consistent significant effects on BP, HR or LSNA compared to vehicle. We also investigated the cardiovascular responses to NaHS microinjected into the RVLM and PVN in SHR rats. Again, there were no significant effects on BP, HR and LSNA. Together, these results suggest that H2S in the RVLM and PVN does not have a major role in cardiovascular regulation.